Gender dan Antikorupsi di Sektor Kehutanan di Kabupaten Sorong Selatan Provinsi Papua Barat - Elsyan Rienette Marlissa; Halomoan Hutajulu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
West Papua's forests are the lungs of the world, because it has the largest remaining forest and it is hoped that its sustainability will be maintained. Community life in the forest has become part of people's lives in South Sorong Regency, West Papua, which is very dependent on natural forests. Forest management activities by local communities are still dominated by men, this is in accordance with the local cultural system which recognizes the patrilineal system which prioritizes men who are more powerful and traditional leadership and village administration than women. Therefore, the issue of gender is very appropriate to be raised and discussed in this research in order to realize equality in adat and leadership in government. In addition, gender issues are linked to the anti-corruption context in the forestry sector in South Sorong Regency. The data used is primary data including data on 1) identity, 2) characteristics of household members, 3) household understanding of forests, 4) gender and forest utilization activities, 5) gender participation in forest management, 6) gender and corruption in forestry sector, and 7) understanding of and participation in the anti-corruption program, while secondary data is in the form of forest area data, Forest Management Units, Forest Farmers Groups, Forest Management Institutions; number of households in forest area, forestry profile of south sorong district, forestry statistics, forestry service annual report. The results of the study show that in terms of gender, men play a greater role in forest management, but also more involved in committing acts of corruption in the forestry sector.Keywords: gender, anticorruption, forest, participation